The intertwining between lead and ethanol in the model organism Caenorhabditis elegans - Albrecht, P. A.; Fernandez-Hubeid, L .E.; Deza-Ponzio, R.; Virgolini, M. B. (Frontiers in Toxicology, 2022)
Caenorhabditis elegans (C. elegans) is a model organism widely used to evaluate the mechanistic aspects of toxicants with the potential to predict responses comparable to those of mammals. We report here the consequences of developmental lead (Pb) exposure on behavioral responses to ethanol (EtOH) in C. elegans. In addition, we present data on morphological alterations in the dopamine (DA) synapse and DA-dependent behaviors aimed to dissect the neurobiological mechanisms that underlie the relationship between these neurotoxicants. Finally, the escalation to superior animals that parallels the observed effects in both experimental models with references to EtOH metabolism and oxidative stress is also discussed. Overall, the literature revised here underpins the usefulness of C. elegans to evidence behavioral responses to a combination of neurotoxicants in mechanistic-orientated studies.